Reflexive Self-Organizing Decision Support Systems for Development Governance - Vladimir, Lepskiy (International Journal of Engineering and Technology, 2018)
In the context of the development of ideas about scientific rationality (classical, non-classical, post-non-classical) the role and diversity of types of reflexive activity in supporting decision makers are justified. The basic types of reflexive activity and reflexive technologies in management are systematized. The trend of transition from control to self-regulation of reflexive activity in self-developing reflexively active environments is grounded.Â Â